What drives Donor Funding in Population Assistance Programs? - Hendrik P. van Dalen; Mieke Reuser (Tinbergen Institute, 2005)
The 1994 International Conference of Population and Development (ICPD) established goals for the expansion of population assistance. This global effort has so far not sufficiently been supported by donor funds. Dynamic panel estimation methods are used to see what lies behind the sharing of burdens and level of donor contributions. Panel data on expenditures for population and AIDS activities have been collected for 21 donor countries for the years 1996-2002. Donor countries are willing to contribute to the ICPD agenda, but those contributions depend heavily on national interests and preferences and to a lesser extent on the development state of less developed countries. Political opportunism in the timing of funds is not strong. With respect to the sharing of the ICPD burden within the group of OECD/DAC countries one can say that on an aggregated scale the burden of population assistance programs is in line with the ability to pay of donor countries. Differences in funding are more connected to other factors such as the size of governments, the state of development of a country and the dominant religions in donor countries.
Keywords: D74; F35; D78; O19; 330; Foreign aid; donors; population policy; collective action; free riding; Entwicklungshilfe; Bevölkerungspolitik; Entwicklungsfinanzierung; OECD-Staaten